Comparative Evaluation of Two Nigerian Local Chicken Ecotypes and Their Crosses for Growth Traits - Momoh, O.M.; Nwosu, C.C.; Adeyinka, I.A. (International Journal of Poultry Science, 2010)
The Nigerian local chickens were grouped on the basis of body size and body weight into Heavy Ecotype (HE) and Light Ecotype (LE). Comparative evaluation of growth traits; Body Weight (BWT), Body Weight Gain (BWG) and Feed Conversion Ratio (FCR) at 4-weekly intervals (from 0-20 weeks) of HE, LE and their F1 crosses; HE x LE - Main Cross (MCX) and LE x HE - Reciprocal Cross (RCX) were carried out. The total of 214, 142, 190 and 185 day-old chicks of HE, LE, MCX and RCX, respectively were used for the study. The chicks in all the genetic groups were raised on deep litter pens from 0-20 weeks using standard management procedures. Data were subjected to analysis of variance. Results showed that the HE differed (p0.05) between the BWT of HE and the crossbred groups as from 8-20 weeks of age. The crossbred groups quickly overcame the initial set backs resulting from maternal/sire-dam interaction effects and grew significantly heavier than the straight bred heavy and light ecotypes during the period, 12-20 weeks of age. FCR showed highly significant (p